Menyiapkan Indonesia Pasca IMF - Harwanto Dahlan (Unisia, 2003)
The writer of the following article explains that Indonesia will end the IMF role at the end of this year. The exit strategy policy that will be conducted by Indonesia emerges debating between pros and conts. But the main problem that should be carry out in this context is how to prepare ways so IMF will not come. The economy crisis in Indonesia actually causes the failure in realizing process of Indonesia government. So the important ways that should be done, Indonesia needs good governance and clean government. In addition, indonesia actually will realize development as trusted by The Constitution 1945.